Rethinking Crime, Harm, and Corporate Responsibility: Lessons from the Post Office Scandal - Drew-Griffiths, Alisse (International Journal of Criminology and Sociology, 2025)
The Post Office Scandal is recognised as one of the most significant miscarriages of justice in British legal history. Using a conceptual review grounded in Zemiological theory this article explores the scandal, arguing that traditional frameworks of criminology fail to capture the full scope of corporate crime. The article begins by tracing the origins of the scandal to the flawed implementation of the Horizon IT system, examining how institutional failures by Fujitsu, the Post Office and the UK Government enabled two decades of systemic injustice. It then applies the theory of Zemiology to challenge dominant constructions of crime, highlighting how the pursuit of profit and poor corporate governance permitted a range of ontological harms to sub-postmasters. The role that inadequate safeguarding in private prosecutions played in the scandal is then considered, drawing comparison to the practices of the RSPCA. Lastly, the article considers the enduring legacy of the scandal and questions whether institutional trust can be rebuilt. The article concludes that whilst reparations and reforms have been made, the Post Office Scandal has caused irreparable damage to the integrity of trusted institutions.